Malaysian English language teachers’ satisfaction level of their professional development - Muhammad Kamarul Kabilan (English Language Teaching and Research Journal (ELTAR-J), 2019)
Professional development is an integral aspect of a teacher’s professional life. Effective professional development activities enable teachers, among others, to update and enhance their pedagogical knowledge and skills, and allow teachers to be creative and critical in their teaching approach. But the question is, to what extent the professional development activities and programmes satisfy the teachers’ needs? This nationwide study aims to determine and identify the level of the Malaysian English language teachers’ level of satisfaction of their professional development – whether English language teachers are satisfied with the professional development experiences and opportunities that are provided by the Ministry of Education and the respective State Education Departments. Schools were randomly chosen and the questionnaires were mailed to the headmasters and principals of the schools to be distributed to all English teachers. A total of 2586 (1038 secondary teachers and 1548 primary teachers) questionnaires were received from teachers all over Malaysia. This paper will highlight and discuss the main findings, and provide some critical implications and suggestions in terms of teacher education and planning and implementation of future professional development activities.